Financial sustainability of state waqf institutions (SWIs) in Malaysia - Sulaiman, Maliah; Alhaji Zakari, Muntaka (Emerald Group Publishing Ltd., 2019)
Purpose: This paper aims to measure the financial sustainability and vulnerability of state-managed waqf institutions in Malaysia. Design/methodology/approach: The study mainly applied the commonly used Tuckman and Chang’s (1991) model to measure the financial health of non-profits. Content and ratio analysis of the 2014 audited reports of seven institutions were used to determine their equity balance, revenue concentration, administrative costs and operating margin ratios. Findings: The results indicate that only one waqf institution was financially sustainable in all the four components. Research limitations/implications: Because the data used are not the latest and focussed only on a single year, the findings may not be necessarily true, currently. Second, the study focussed only on Malaysia. Thus, the results may not be generalisable to other waqfs in other countries or to privately managed waqf institutions. Accordingly, future research should address these limitations. Practical implications: The findings provide useful insights into the financial sustainability of waqf institutions and highlight the need for policymakers in Malaysia and other Muslim countries to give due attention to the holistic accountability of waqf institutions to ensure waqf’s systematic revival. Originality/value: The paper, being the first to investigate the financial sustainability and vulnerability of state waqf institutions in Malaysia, serves as a reference for future researchers. © 2019, Emerald Publishing Limited.